2011
DOI: 10.1111/j.1365-2184.2011.00747.x
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro study of enhanced osteogenesis induced by HIF-1α-transduced bone marrow stem cells

Abstract: These results indicate that Lenti-HIF-1α can induce BMSC overexpression levels of angiogenic and osteogenic genes in vitro in the normoxic state. Further study will be focused on whether HIF-1α can also improve bone repair in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 40 publications
(42 reference statements)
2
56
0
Order By: Relevance
“…12,13 Previous studies have demonstrated that hypoxia-inducible factor (HIF) influences mesenchymal cells to differentiate along the osteoblast pathway, in part through activating osterix gene expression. 14,15 HIF is also an active nucleoprotein that enhances the production of corresponding proteins, thereby launching the process of angiogenesis. 16 It is therefore proposed that this agent could promote the DO process by simultaneously enhancing osteogenesis and angiogenesis.…”
mentioning
confidence: 99%
“…12,13 Previous studies have demonstrated that hypoxia-inducible factor (HIF) influences mesenchymal cells to differentiate along the osteoblast pathway, in part through activating osterix gene expression. 14,15 HIF is also an active nucleoprotein that enhances the production of corresponding proteins, thereby launching the process of angiogenesis. 16 It is therefore proposed that this agent could promote the DO process by simultaneously enhancing osteogenesis and angiogenesis.…”
mentioning
confidence: 99%
“…The housekeeping gene, GAPDH, was used for normalization. 25,26 The specific primer sequences used in this study are listed in Table 1.…”
Section: Reverse Transcription and Real-time Pcr Assaymentioning
confidence: 99%
“…26,27 A semiquantitative analysis of alkaline phosphatase and calcium deposition was performed as previously described. 25 Alkaline phosphatase activity was determined by measuring the OD values for absorbance at 405 nm after incubation with p-nitrophenyl phosphate (Sigma) for 30 minutes at 37°C. For quantification of Alizarin Red S, the stained samples were desorbed using 10% cetylpyridinium chloride (Sigma), and the OD values for absorbance of the eluent were determined at 590 nm.…”
Section: Cell Adhesion Ability Assaymentioning
confidence: 99%
“…32,33 A semiquantitative analysis of alkaline phosphatase was performed as previously described. 34 Alkaline phosphatase activity was determined by measuring the optical density values for absorbance at 405 nm after incubation with p-nitrophenyl phosphate (Sigma-Aldrich, St Louis, MO, USA) for 30 minutes at 37°C. The intracellular total protein content was determined using the Micro BCA protein assay kit (Thermo Fisher Scientific, Waltham, MA, USA), and the alkaline phosphatase activity was normalized to the total protein content.…”
Section: Cell Morphology and Proliferationmentioning
confidence: 99%